THE EFFECT OF ISLAMIC BRANDING ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A VARIABLE INTERVENING CASE STUDY: BSI KC CIREBON SILIWANGI - Diana Magfiroh (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
This study was shown to determine whether there is an influence of Islamic branding and customer satisfaction on customer loyalty at BSI KC Cirebon Siliwangi . This study uses quantitative methods with a sample size of 100 respondents. Sampling using Slovin technique with purposive sampling method . The data analysis techniques used in this study include the research instrument test, classical assumption test, hypothesis testing , path analysis and coefficient of determination test. Based on the calculation of the t test ( by partial ) Islamic branding has a positive and significant influence on customer loyalty. Islamic branding has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant influence on customer loyalty. Islamic branding has a positive and significant influence on customer loyalty which is mediated by customer satisfaction at BSI Cirebon Siliwangi Cirebon customers. Based on the calculation of the f test (simultaneously) customer satisfaction and Islamic branding on customer loyalty has a calculated f value greater than f table and a significance value of 0.000 <0.05. Which means, Islamic branding and customer satisfaction variables affect customer loyalty together.